Grain size and grain size distribution of a lithified fault core in carbonates rocks using multi-scale image analysis: The example of the San Benedetto-Gioia dei Marsi fault (Central Italy). (May 2020) - Merico, A.; Iezzi, G.; Pace, B.; Ferranti, L.; Cremona, M.; Scafa, M.; Cavallo, A.; Colella, A.; Nazzari, M.; Scarlato, P.
Abstract: Analyses of three oriented rock samples collected in the footwall of a major normal fault in Central Italy provide insights into textural properties of a lithified carbonate fault core. Data from lithified fault rocks are very rare and we document here the grain size distribution in a fault core at an unprecedented scale range, which complements already existing observations obtained from sieve, sedimentation and/or laser diffraction methods in loose deposits. X-ray powder diffraction analysis shows that the samples, which are located at a mutual distance of few tens of meters, are exclusively made of calcite. Mesoscopic samples and polished thin sections oriented normal to the fault plane have been analysed with high resolution scanner (HRS), transmission optical microscopy (TOM) and scanning electron microscopy in back-scattered mode (BS-SEM). Textural features of tectonised calcite crystals have been quantified using image analysis on digitalised photographs at magnifications from 1:1 to 9000:1, documenting size dimensions of grains from cm to sub-μm. The obtained D values have average values of 1.65 in 2D, overlapping with those independently obtained by box-counting methods in the core of the same fault by previous authors. Textures of calcite clasts in tectonised and lithified rocks can be appropriately quantified by the analytical protocols proposed here. This work represents the first multi-scale image analysis, from sub- μm to cm sizes, of the core portion of a normal fault that cut into carbonate rocks. Our study provides a template for similar investigations to be carried on other faults that will help to better understand the relations between fault textures and deformation processes. Highlights: Rock surface cut normal to fault planes can be the key feature to compare different faulted samples. Textures of tectonised calcite clasts can be statistically measured applying 2D imaging methods. Quantitative textures of tectonised calcite clasts by TOM and SEM are virtually identical. Grain-size distributions and log D vs log N plots can be attained using the analytical protocols. The D-values obtained are in agreement with those obtained by the box counting methods.